FINITE ELEMENT ANALYSIS OF FRICTION PARAMETERS ON 6060 ALUMINIUM ALLOY IMPRESSION DIE COLD FORGING PROCESS - POP, M.; FRUNZA, D. (Studia Universitatis Babeș-Bolyai Physica, 2016)
In this paper cold forging process of aluminium alloy 6060 is simulated and analyzed at different stages of forging and with different quality of lubricants. Finite element (FE) method is extensively employed in solving linear and non-linear problems and widely used particularly in analyzing a forming process. Three-dimensional modeling of initial material and die are performed by Solid Works, while simulation and analysis of forging are performed by Forge. Based on the computer simulation the required dies are designed and the workpieces are formed.